Sappho in Lyric IV: Michael Field’s Spatial Poetics of Desire and Defeat - Cantillo-Lucuara, Mayron Estefan (Miscelánea: A Journal of English and American Studies, 2021)
In this article, I offer a close reading of Michael Field’s Long Ago (1889), specifically of lyric IV, with the primary aim of showing how Katharine Bradley and her niece Edith Cooper appropriate the archaic figure of Sappho, dramatise her Ovidian romantic tragedy and, in so doing, reconceptualise the notional category of space in two complementary ways: on the one hand, lyric space becomes a tense locus of contention between form-as-hope and content-as-despair and, on the other, the correlation established between space, nature and gender results in a transgressive topography in which, as I conclude, a new Sappho emerges both as a tragic heroine and as an extremely possessive consciousness laden with sheer Hegelian desire.